ACTIVE MODERN NEOLOGISMS IN OUR SPEECH APPLICATION - Nilufar, Urazimbetova (PT. Antis International Publisher, 2024)
This article describes the classification of neologisms that have recently entered our language and their activity in speech. Neologisms in the article are mainly borrowed from Russian and EnglishAdd Contributor